Hands-On information security lab manual - Michael E. Whitman (Course Technology, Cengage Learning, 2006)
The Hands-On Information Security Lab Manual, Second Edition allows students to apply the basics of their introductory security knowledge in a hands-on environment with detailed exercises using Windows 2000, XP and Linux. This non-certification based lab manual includes coverage of scanning, OS vulnerability analysis and resolution firewalls, security maintenance, forensics, and more. A full version of the software needed to complete these projects is included on a CD with every text, so instructors can effortlessly set up and run labs to correspond with their classes. The Hands-On Information Security Lab Manual, Second Edition is a suitable resource for introductory, technical and managerial courses, and is the perfect accompaniment to Principles of Information Security, Second Edition and Management of Information Security